DIVERSITAS TANAMAN PEKARANGAN SEKOLAH SEBAGAI BAHAN AJAR MATERI KEANEKARAGAMAN HAYATI PADA KELAS VII DI SEKOLAH MENENGAH PERTAMA - Novinovrita, Novinovrita; Nurhasnah, Nurhasnah (Natural Science: Jurnal Penelitian Bidang IPA dan Pendidikan IPA, 2018)
This study aims to determine the diversity of plants in the school yard, knowing the use of garden plants as teaching materials on biodiversity material, and knowing the constraints and solutions in the use of garden plants as teaching material on biodiversity material in 34 KerinciState Junior High School. This is qualitative research by observing directly in the field. The object of research is the diversity of school yard plants as a material for biodiversity teaching materials in class VII. Research data comes from the principal, teacher and students as the object of research. Data collection techniques are observation, interviews, and documentation. Data analysis is carried out in three stages. The first stage of data analysis during data collection took place, the second stage was carried out after data collection and the third stage was advanced data analysis in the form of data presentation.The results showed the diversity of school yard plants in Kerinci 34 State Junior High School there were 33 species with 18 families. Most families are Araceae and Euphorbiaceae. School yard plants in Kerinci 34 State Junior High School are used as teaching materials by taking photos of plants directly, the plants are classified so that they can be known of species or families, photos and results of the classification are made in the form of visual teaching materials in the form of pictures and applied to students. The obstacle experienced is that it takes a long time, the lack of interest of students to know the scientific name of each type of plant in the schoolyard, and the lack of clear communication between teachers and students. In applying teaching materials for school yard plants in 34 Kerinci State Junior High School, biology teachers collaborate with school personnel and students to overcome the obstacles faced by giving scientific names in each type of plant in Kerinci 34 State Junior High School, reminding students to really pay attention when the teacher applies the teaching materials of the school yard, and evaluate the results of the application of school yard teaching materials in the biodiversity lesson material, especially plant diversity.